Minced Umbilical Cord Fragments as a Source of Cells for Orthopaedic Tissue Engineering: An In Vitro Study. (7th March 2012) - Marmotti, A.; Mattia, S.; Bruzzone, M.; Buttiglieri, S.; Risso, A.; Bonasia, D. E.; Blonna, D.; Castoldi, F.; Rossi, R.; Zanini, C.; Ercole, E.; Defabiani, E.; et al.
Abstract : A promising approach for musculoskeletal repair and regeneration is mesenchymal-stem-cell- (MSC-)based tissue engineering. The aim of the study was to apply a simple protocol based on mincing the umbilical cord (UC), without removing any blood vessels or using any enzymatic digestion, to rapidly obtain an adequate number of multipotent UC-MSCs. We obtained, at passage 1 (P1), a mean value of 4, 2 × 10 6 cells (SD 0, 4) from each UC. At immunophenotypic characterization, cells were positive for CD73, CD90, CD105, CD44, CD29, and HLA-I and negative for CD34 and HLA-class II, with a subpopulation negative for both HLA-I and HLA-II. Newborn origin and multilineage potential toward bone, fat, cartilage, and muscle was demonstrated. Telomere length was similar to that of bone-marrow (BM) MSCs from young donors. The results suggest that simply collecting UC-MSCs at P1 from minced umbilical cord fragments allows to achieve a valuable population of cells suitable for orthopaedic tissue engineering.